Repair Effects of Scenedesmus obliquus on Cucumber Seedlings Under Saline–Alkali Stress - Zhao Liu; Yanlong Dong; Xiaoxia Jin; Yan Liu; Zhonghui Yue; Wei Li (Agronomy)
In this study, cucumber seedlings were treated with Scenedesmus obliquus at different concentrations (0.25, 0.50, 0.75, 1 g·L−1) under saline–alkali stress (60 mM and 90 mM). The effects of Scenedesmus obliquus on the repair of cucumber seedlings under saline–alkali stress were explored from physiological and morphological perspectives by measuring growth physiological indices and observing microstructure. It provides a cytological basis for the development of microalgae biofertilizer. The results showed that the addition of Scenedesmus obliquus effectively alleviated the physiological and structural damage in cucumber seedlings caused by saline–alkali stress, with the best mitigation effect at 0.75 g·L−1. More specifically, the addition of Scenedesmus obliquus significantly improved seedling fresh weight and plant height under saline–alkali stress, increased stem vascular vessel diameter, thickened vessel walls, reduced structural damage, the structural recovery of mitochondria, nuclei, and other organelles in the phloem; The results showed that root xylem vessel distribution became more centralized, vessel diameter decreased, and wall thickness decreased, with other changes similar to those in the stem; The number and volume of mesophyll cells increased, chloroplast morphology recovered, and chlorophyll content rose, effectively alleviating the impact of saline–alkali stress on photosynthesis. MDA content decreased, mitigating oxidative damage caused by saline–alkali stress.